Marketing Strategies of Travel and Tourism Industry - Ganatra, Varsha; Utama, A.A. Gde Satia; Pawar, Purvika; Verma, Sahil; Pandey, Rudresh; Whiryawan, Jhonathan; Sin, Liem Gai; Ling, Chong Chiew; Kee, Daisy Mui Hung; Jin, Chai Yeong; Min, Tan Hui; Chen, Lim Sin (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
Travel and Tourism is an assemblage of all the leisure, luxuries, comfort, travel products, and services provided by suppliers including airlines, hotels, transportation like self-drive agencies, cruise lines, restaurants, etc. All these functions require marketing. This study aims to explore the marketing patterns of tourist agencies to increase customer awareness. The tourism sector also helps to promote the various hotels, restaurants, rental agencies by giving a platform for all these services to promote their services and also provide a customer discount for customer satisfaction.